Concept, design, and energy analysis of an integrated power-to-methanol process utilizing a tubular proton-conducting solid oxide electrolysis cell. (17th May 2019) - Schwabe, Felix; Schwarze, Louisa; Partmann, Christine; Lippmann, Wolfgang; Hurtado, Antonio
Abstract: An alternative power-to-methanol process based on an integration of a tubular proton-conducting solid oxide electrolysis cell into a methanol synthesis unit is explained, energetically evaluated and technically presented. Being currently developed in the joint research project DELTA, the novel process has the potential for a significant increase in system efficiency, if the heat from the exothermic synthesis reaction can be utilized and/or kinetic advantages can be achieved. For the experimental proof of the concept and a comprehensive characterization of the process, a test platform is currently under construction. The design of the flexible test facility with the complex technical integration of both processes (electrolysis and synthesis) is described briefly. The chemical reactor, where electrolysis and synthesis are taking place, allows for an operation at temperatures (for electrolysis) up to 700 °C, pressures of 10 MPa and a current (across the electrolysis cell) of up to 100 A. Moreover, a precise pressure balancing system between both gas volumes, an axial temperature measurement and the possibility of regulating both processes inside the pressure vessel are pivotal properties of the test facility. Graphical abstract: Image 1 Highlights: Integration of a proton-conducting SOEC into a synthesis unit. Theoretical energetic efficiency increase of approx. 6%. Engineering of testing facility for 700 °C and 10 MPa.